Infiltrasi Motif Buburi Olimpopo pada Desain Motif Nusa Tenggara Timur sebagai Inovasi Desain Tekstil - Devo Christofel Medah; Ariency K. A. Manu; Efraim Jehane Pranamantara; Napsiyana A. Weo; Fathurrahmaniah Fathurrahmaniah; Rima Nindia Selan (Universitas Nusa Cendana, 2026)
This study investigates digital textile design innovation through a cultural infiltration approach, integrating the visual elements of the Buburi Olimpopo Motif from Bombana Regency, Southeast Sulawesi into the structure of three East Nusa Tenggara (NTT) motifs: the Kaif Motif (Timor), the Sepe Motif (Kupang), and the Ntala Motif. The method employed is Research and Development (R&D) using the PPE Model (Planning, Production, Evaluation), integrated with a qualitative approach in a Concurrent Embedded design. The Planning phase produced differentiated infiltration concepts for each base motif through literature study and design needs analysis. The Production phase yielded three digital design prototypes developed using Affinity Designer software with a CMYK color profile. In Design I, Buburi Olimpopo spiral elements were inserted into the four-pointed star void of the Kaif Motif using a charcoal-silver monochromatic palette. In Design II, the organic elements of the Sepe Motif were merged with Buburi Olimpopo using red, emerald green, and navy blue palettes. In Design III, the empty star core of the Ntala Motif was entirely reconstructed by Buburi Olimpopo using a metallic gold and ruby red palette. All three prototypes consistently applied Gestalt principles of unity and harmony, demonstrating that the infiltration method produces a new cultural composition distinctly different from conventional patchwork approaches.